Entrepreneurial orientation and innovative performance in SMEs: the role of organizational learning - Hernández-Ramírez, Manrique (2021)
This study analyzes the effect of organizational learning capacity on the relationship between entrepreneurial orientation and innovative performance among SMEs. The data was drawn from a sample of 158 SMEs coming from a research project at the Costa Rica Institute of Technology. The results of the sequential hierarchical regression models indicate that both entrepreneurial orientation and organizational learning capacity, in general, positively affect SMEs’ innovative performance. In addition, the findings reveal that organizational learning capacity conditions the effect of entrepreneurial orientation on innovative performance, thus suggesting that the effect of entrepreneurial orientation on innovative performance is enhanced in SMEs with a greater learning capacity. The results highlight the importance of practices that facilitate organizational learning such as experimentation, risk-taking, interactions with the external environment, dialogue, and participatory decision-making in SMEs.